Rancang Bangun Antena Sektoral MIMO Pada Jaringan GSM 900 MHz Menggunakan Radio BladeRF - Saputra, Dwi Indra; Hesti, Emilia; Soim, Sopia (Patria Artha Technological Journal, 2022)
MIMO sectoral antennas are antennas that are often used and installed in BTS towers owned by cellular operators. The sektral antenna is useful for GSM, GPRS, and LTE communications. The gain generated by sectoral antennas is quite large compared to other antennas. As well as the resulting radiation pattern can select the area that can be reached. This research designs and builds a sekotral antenna with a working frequency of 900 MHz which will be used as a transmitter for bladeRF as the main radio. Designing and simulating the antenna is carried out on the MMANA-GAL software application. In order to get the desired parameters and results and to know the parameters of the antenna, it is necessary to design the antenna first. The parameters that will be obtained when measuring sectoral antennas in this research are SWR, Gain, radiation pattern, polarization, and impedance. After taking measurements and simulations, it is found that the difference in the results obtained from the experiment is that the performance of sectoral antennas is very good and can be used on real radio or in real conditions in the field. In the 4-element simulation, the SWR generated during the simulation is 1.22, the resulting gain is 13.17, the resulting impedance is 57.87, and the radiation pattern has an angle of 60o. Meanwhile, when testing using the Antenna Network Analyzer, it can only determine 3 parameters, namely impedance, SWR, and smitch chart. The resulting SWR is 1.4 which is not the same as the MMANA-GAL simulation results, then there is an impedance which has a good value of 54.6. Which value is close to the value of 50 but in the simulation the value obtained is greater. The thing that affects the values of these parameters is because during the simulation the array elements should be circular but instead formed a rectangle and the measuring instrument used is also still unstable when measuring in real terms on the antenna. This sectoral antenna can be used properly in GSM technology telephone communication at a working frequency of 900 MHz which will be used in the Software Defind Radio BladeRF